Review articleThe role of T-cell subpopulations in psoriasis - Nedoszytko, Bogusław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
The pathogenesis of psoriasis is still an unresolved problem. The dysregulation of innate and adaptive skin defence mechanisms plays a main role in the induction of psoriatic lesions. There is clear evidence that T-cells have a central role in psoriasis, but the role of subpopulations of such cells is still debated. The aim of this article is to describe the participation in the pathogenesis of psoriasis of T helper lymphocytes, NK and NK-T cells, TCRγδ lymphocytes, regulatory T cells, CD8+ suppressors cells, and the newly described population of Th17 cells.